PROCESSO DE (RE)MATRÍCULA DA UNIJUÍ NA PERCEPÇÃO DOS COLABORADORES: FRAGILIDADES E POTENCIALIDADES - LAZZAROTTO, ELENIR D. R.; FOLLAK, LEILA R. C.; FROEMMING, LURDES M. S.; CARVALHO, ROGÉRIO N. D. (Salão do Conhecimento, 2013)
Resumo